Probabilistic scheduling algorithm for providing proportional delay differentiation in content-based online charging system - HUANG Hai1; LIAO Jian-xin1; ZHU Xiao-min1; ZHANG Le-jian1; YANG Ge2 (Tongxin xuebao)
A novel request scheduling algorithm was proposed for the OCS （online charging system） server. The basic idea is that one of the requests from all classes of service queues is scheduled with some priority probability which is based on the system queue-length, the request arrival rate, and the pre-assigned delay differentiation parameter. The experimental results show that, in considering request service delays, this proposed algorithm always outperforms some other traditional PDD （proportional delay differentiation） scheduling ones and the performance advantages are relatively greater when request service delays increase and vary greatly from each other. Furthermore, it can efficiently meet 6 QoS （quality of service） requirements proposed in content-based billing.